2‐mm surgical margins are adequate for most basal cell carcinomas in Japanese: a retrospective multicentre study on 1000 basal cell carcinomas. (9th February 2020) - Nakamura, Y.; Matsushita, S.; Tanaka, R.; Saito, S.; Araki, R.; Teramoto, Y.; Aoki, M.; Yamamura, K.; Nakamura, Y.; Fujisawa, Y.; Brinker, T.J.; Yamamoto, A.
Abstract: Background: Surgery is the gold standard for basal cell carcinomas (BCC). Current recommended surgical margins for BCCs are determined from studies in Caucasian populations. However, the appropriate surgical margins for BCCs in non‐white races are unclear. Objectives: To investigate the accuracy of preoperative determination of clinical tumour borders and appropriate surgical margins in Japanese patients with BCC. Methods: The maximum calculated differences in distance between the preoperatively determined surgical margins and the actual histologic tumour side margins were considered as 'accuracy gaps' of clinical tumour borders. Estimated side margin positivity rates (ESMPRs) with narrower (2 and 3 mm) surgical margins were calculated on the basis of the accuracy gaps. Results: Overall, 1000 surgically excised BCCs from 980 Japanese patients were included. The most frequent histologic subtype was nodular BCC (67%). The median accuracy gap was 0.3 mm [interquartile range (IQR): −0.5 to +1 mm]. The ESMPRs with 2‐ and 3‐mm surgical margins were 3.8% and 1.4%, respectively. Only the ESMPRs between the well‐defined ( n  = 921) and poorly defined clinical tumour border groups ( n  = 79) showed statistical difference [2‐mm margin: 3.1% vs. 11.7%, OR: 3.89, 95% confidential interval (CI): 1.41–10.71, P <0.01; 3‐mm margin: 0.97% vs. 6.3%, OR: 6.58, 95% CI: 1.67–25.99, P <0.01]. No significant differences in ESMPRs were noted in other subgroups including risk classifications. Conclusions: The determined clinical tumour border accuracy gaps in this Japanese cohort were negligible. Dermatologic surgeons may use narrower surgical margins with acceptable margin positivity rates. The clarity of clinical tumour borders could be an appropriate guide for selection of different surgical margins in the Japanese cohort.